Search for WH associated production in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Aoki, M.; Askew, A.; Åsman, B.; et al. (American Physical Society (APS), 2012)
This report describes a search for associated production of W and Higgs bosons based on data corresponding to an integrated luminosity of L≈5.3fb -1 collected with the D0 detector at the Fermilab Tevatron pp̄ Collider. Events containing a W→ν candidate (with corresponding to e or μ) are selected in association with two or three reconstructed jets. One or two of the jets are required to be consistent with having evolved from a b quark. A multivariate discriminant technique is used to improve the separation of signal and backgrounds. Expected and observed upper limits are obtained for the product of the WH production cross section and branching ratios and reported in terms of ratios relative to the prediction of the standard model as a function of the mass of the Higgs boson (M H). The observed and expected 95% C.L. upper limits obtained for an assumed M H=115GeV are, respectively, factors of 4.5 and 4.8 larger than the value predicted by the standard model. © 2012 American Physical Society.